Diagnostic Accuracy of the Progressive Collapsing Foot Deformity (PCFD) Classification. (June 2022) - Li, Shuyuan; Zhu, Mingjie; Gu, Wanjun; Hamati, Mary; Hunt, Kenneth J.; de Cesar Netto, Cesar; Simonson, Tatum S.; Myerson, Mark S.
Background: A consensus group recently proposed the term progressive collapsing foot deformity (PCFD) and a new classification with 2 stages plus 5 classes to describe the complex array of flatfoot deformities. This study aimed to validate different diagnostic accuracy rates of the PCFD classification. Methods: This was a survey-based study distributed among 13 foot and ankle fellowship programs for 3 groups of participants with varied experience in practice (group 1: fellows in training, group 2: surgeons in practice for 1-4 years, and group 3: surgeons in practice for ≥5 years). Each participant was asked to assign 20 different cases of flatfoot deformity to the appropriate classes and stages using the PCFD classification. The overall diagnostic accuracy, class, and stage diagnostic accuracy rates for the 20 cases were calculated first for the entire cohort and then compared among the 3 groups. The misdiagnosis rate for each class of deformity (the sum of overdiagnosis and underdiagnosis rates) of the entire cohort was calculated and compared with the other classes. Mean and standard evidence were used to describe numerical data. One-way analysis of variance was used to compare values among the 3 groups and the 5 classes. P <.05 was considered statistically significant. Results: For the whole cohort, the overall diagnostic accuracy, class diagnostic accuracy, and stage diagnostic accuracy rates were 71.0%, 78.3%, and 81.7%, respectively There was a statistically significant difference between group 1 and 2, and group 1 and 3, in overall diagnostic accuracy and class diagnostic accuracy, with no significant difference among the 3 groups regarding stage diagnostic accuracy. Class B had a significantly higher overdiagnosis rate than the rest of the classes, whereas class D was significantly underdiagnosed than others. The misdiagnosis rates for classes A to E were 3.3%, 17.5%, 11.1%, 26.0%, and 3.7%, respectively. Conclusion: The PCFD classification showed overall fair diagnostic accuracy rates. The highest diagnostic accuracy was for "hindfoot valgus deformity" and "ankle instability." Further content validation of the PCFD classification is needed to examine the terminology and interpretation of those classes with low diagnostic accuracy including "midfoot/forefoot abduction deformity, " "forefoot varus deformity/medial column instability, " and "peritalar subluxation/dislocation." Level of Evidence: Level II, prospective comparative study.